1987
DOI: 10.1007/bf02554334
|View full text |Cite
|
Sign up to set email alerts
|

Late development of metachronous colorectal cancer

Abstract: The incidence of metachronous colorectal cancer has been reported to be 1 to 5 percent, with most of the cases being discovered within ten years of the initial cancer. A retrospective review of all colorectal cancer patients was conducted at the Southern Illinois University Affiliated Hospitals to determine the incidence of metachronous colorectal cancer at the authors' institution. In this study, a metachronous cancer was defined as a second colorectal primary occurring at least three years following discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…A similar definition was used in four other studies1, 7–9. In six further studies, cancers diagnosed within a year of the initial diagnosis were classified as synchronous3, 4, 6, 18–20 and, in another, those diagnosed within 3 years21. Discrepancies may also result from the size of the studied populations, population characteristics (excluding or not excluding ulcerative colitis and genetic syndrome), and the period studied.…”
Section: Discussionmentioning
confidence: 99%
“…A similar definition was used in four other studies1, 7–9. In six further studies, cancers diagnosed within a year of the initial diagnosis were classified as synchronous3, 4, 6, 18–20 and, in another, those diagnosed within 3 years21. Discrepancies may also result from the size of the studied populations, population characteristics (excluding or not excluding ulcerative colitis and genetic syndrome), and the period studied.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Although the updated society guidelines 7-10 include recommendations on the surveillance intervals after CRC surgery, the proportion of a second primary CRCdfurther referred to as metachronous CRC (mCRC)ddid not decrease over the past decade, ranging from 1% to 4% of all patients with CRC. [11][12][13][14][15][16][17][18][19] In the early 80s, Tornqvist et al 11 found that mCRCs account for 2.1% of all CRCs, in a cohort of curatively treated patients with CRC. Two decades later, Green et al 12 found 42 mCRC cases over 15,000 person-years of follow-up, corresponding to a proportion of 1.3%.…”
mentioning
confidence: 98%
“…Although only 1 sample from each site was examined in this study, the sensitivity of our method might be increased by obtaining more specimens. Metachronous colorectal cancer has been reported to be relatively frequent (1.1–4.8% of colorectal patients) with most second primaries being discovered within 10 years of the initial colorectal cancer 31, 32. We found K‐ ras mutations in normal mucosa samples from some patients who had undergone colorectal tumor resections more than 1 year before.…”
Section: Discussionmentioning
confidence: 77%